The talking eggs a folktale from the American South - San Souci, Robert D.; Pinkney, Jerry (New York Dial Books, 1989)
A Southern folktale in which kind Blanche, following the instructions of an old witch, gains riches, while her greedy sister makes fun of the old woman and is duly rewarded.
Keywords: Folklore -- United States